Report on a New Opioid NPS: Chemical and In Vitro Functional Characterization of a Structural Isomer of the MT-45 Derivative Diphenpipenol. Issue 2 (6th June 2020) - Cannaert, Annelies; Hulpia, Fabian; Risseeuw, Martijn; Van Uytfanghe, Katleen; Deconinck, Eric; Van Calenbergh, Serge; Blanckaert, Peter; Stove, Christophe
Abstract: In this paper, the identification and full characterization of a novel non-fentanyl opioid sourced online, which is a member of the 1-substituted-4-(1, 2-diphenylethyl)piperazine derivatives related to MT-45, is reported. The sample was sold under the name "diphenpipenol, " (3-[2-[4-(2-methoxyphenyl)piperazin-1-yl]-2-phenylethyl]phenol), although extensive NMR analysis showed that the product obtained was actually a diphenpipenol structural isomer, (2-[4-(2-methoxyphenyl)piperazin-1-yl]-1, 2-diphenylethanol). Liquid chromatography time-of-flight mass spectrometry identified an exact mass for the protonated molecule of m/z 389.2264, with two prominent fragment ions ( m/z 91.0567 and 150.0937), which were not reported in earlier literature describing MT-45 derivatives. The chemical characterization was finalized by gas chromatography–mass spectrometry, high-performance liquid chromatography diode array detector and Fourier-transform infrared spectroscopy analyses. This product is a clear example of the trend that new non-fentanyl opioids are reappearing on the recreational drug market to escape the recent changes in (inter)national legislation concerning fentanyl analogues. Although in this particular case, the product's potency and efficacy were relatively low, other new non-fentanyl opioids might possess stronger potencies and therefore pose greater health risks for ignorant users. The fact that the product was sold under the wrong name further demonstrates the well-known problematic issue of a mismatch between the adverted and true identity, confirming the irregularities of the online new psychoactive substances market.